Perceptions of medical students about Pathology training (Journal of Pathology of Nepal, 2021)
Background: An understanding of pathology is the foundation for good clinical practice. Pathology is a vast subject with limited teaching hours. Understanding the students' perspectives is essential for making new roadmaps for teaching.Materials and methods: This is a survey conducted on medical students who have completed second-year. They were asked to answer a pre-validated questionnaire regarding the teaching-learning and assessment methods followed in the pathology department.Results: Of the 152 students, the majority (84%) of students perceived pathology as an interesting subject. Most (87%) of the students agreed that the integration of pathology teaching with clinical training helped in a better understanding of diseases. Many (54%) students found general pathology to be difficult than systemic pathology. Most of the students agreed that lectures and demonstrations are taken in ways that stimulate interest in the subject. The majority were of the consensus that appropriate clinical correlation was done during lectures along with highlighting essential points. Regarding the teaching tools used in pathology, 55% of the students preferred teaching by PowerPoint presentation only while 45% preferred a combined blackboard and PowerPoint presentation. Many considered that integrated teaching helps in a better understanding of the subject.  The formative method of assessment was favoured by most of the students. Our study showed that 74% of students find multiple-choice questions as an effective assessment tool.Conclusions:  As the new curriculum for competency-based medical education is through, the result of our study is an encouragement to be prepared for the same.